Higher thyroid hormone receptor expression correlates with short larval periods in spadefoot toads and increases metamorphic rate - Hollar, Amy R. (2011)
Spadefoot toad species display extreme variation in larval period duration, due in part to evolution of thyroid hormone (TH) physiology. Specifically, desert species with short larval periods have higher tail tissue content of TH and exhibit increased responsiveness to TH. To address the molecular basis of larval period differences, we examined TH receptor (TR) expression across species. Based on the dual function model for the role of TR in development, we hypothesized that desert spadefoot species with short larval periods would have 1) late onset of TR expression prior to the production of endogenous TH and 2) higher TR levels when endogenous TH becomes available. To test these hypotheses, we cloned fragments of TRα and TRβ genes from the desert spadefoot toads Scaphiopus couchii and Spea multiplicata and their non-desert relative Pelobates cultripes and measured their mRNA levels in tails using quantitative PCR in the absence (premetamorphosis) or presence (natural metamorphosis) of TH. All species express TRα and TRβ from the earliest stages measured (from just after hatching), but S. couchii, which has the shortest larval period, had more TRα throughout development compared to P. cultripes, which has the longest larval period. TRβ mRNA levels were similar across species. Exogenous T3 treatment induced faster TH-response gene expression kinetics in S. couchii compared to the other species, consistent with its increased TRα mRNA expression and indicative of a functional consequence of more TRα activity at the molecular level. To directly test whether higher TRα expression may contribute to shorter larval periods, we overexpressed TRα via plasmid injection into tail muscle cells of the model frog Xenopus laevis and found an increased rate of muscle cell death in response to TH. These results suggest that increased TRα expression evolved in S. couchii and contribute to its higher metamorphic rates.